Production of thermostable L2 lipase from bacillus sp. - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Sabri, Suriana; Mohd Shariff, Fairolniza (2007)

(untitled)
L2 lipase is a unique purified thermostable recombinant lipase enzyme from Bacillus sp L2. It is highly recommended for industrial applications which require high temperature processes. It can catalyze hydrolysis of triglycerides, esterification, transesterification, polymerization and lactonization.